Reading John and 1, 2, 3 John a literary and theological commentary - Myers, Alicia D. (Macon Smyth & Helwys Publishing, Inc, 2019)
"Reading John and 1, 2, 3 John seeks to help readers-whether students or scholars, ministers or laypeople-gain a greater understanding of and appreciation for biblical texts in their original contexts. To this good end, commentaries in this series attend not only to lexical, historical, and critical concerns but are also attuned to and interested in, as the subtitle of each volume signals, literary matters and theological meaning"--
Includes bibliographical references
Keywords: Bible -- Commentaries; Bible -- Commentaries; Kommentar